2006
DOI: 10.1158/0008-5472.can-05-4569
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Growth and Elimination of Multiple Metastases in Human Prostate and Breast Xenografts by Systemic Inoculation of a Host Defense–Like Lytic Peptide

Abstract: We report on a short host defense-like peptide that targets and arrests the growth of aggressive and hormone-resistant primary human prostate and breast tumors and prevents their experimental and spontaneous metastases, respectively, when systemically inoculated to immuodeficient mice. These effects are correlated with increased necrosis of the tumor cells and a significant decrease in the overall tumor microvessel density, as well as newly formed capillary tubes and prostate-specific antigen secretion (in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 43 publications
7
112
0
Order By: Relevance
“…Their mode of action can vary. It was shown that they can induce necrosis after plasma membrane disruption, depending on their L-or D-chirality, 52,53 apoptosis by the upregulation of caspases, 54 the influx of extracellular Ca 2 + , Ca 2 + -mediated DJm disruption and mitochondrial O 2 $ À generation. 55 However, the cationic peptide (KLAKLAK) 2 has been reported to have a potency that is too low for it to be used as an effective anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…Their mode of action can vary. It was shown that they can induce necrosis after plasma membrane disruption, depending on their L-or D-chirality, 52,53 apoptosis by the upregulation of caspases, 54 the influx of extracellular Ca 2 + , Ca 2 + -mediated DJm disruption and mitochondrial O 2 $ À generation. 55 However, the cationic peptide (KLAKLAK) 2 has been reported to have a potency that is too low for it to be used as an effective anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Cetuximab adds to the compounds able to inhibit primary tumor growth and metastasis. For example, Papo and colleagues (39) observed that host defense-derived cytolytic cationic polypeptides kill cancer cells via cytoplasmic membrane depolarization, and the resulting membrane disruption can provide a therapeutic means of inhibiting both tumor growth and metastasis of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then incubated for 2 h before adding to each well 50 ml 2,3-bis-2H-tetrazolium-5-carboxanilide inner salt reaction solution (Biological Industries). Viability was determined as described previously (19,20). The LC 50 (the concentration at which 50% of the cells die) for each peptide was obtained from the dose-dependent cell viability curves.…”
Section: -Bis-2h-tetrazolium-5-carboxanilide Inner Salt Cytotoxicimentioning
confidence: 99%